The climate impact and land use of cultivated meat: Evaluating agricultural feedstock production. - Hanno Kossmann; Thorsten Moess; Peter Breunig (PLoS ONE)
As global demand for meat continues to rise, alternative and sustainable methods of production are being explored. Cultivated meat (CM) is one such alternative that holds potential for sustainable production with less environmental impact. This study develops an approach to evaluate CM production based on agricultural feedstock. The specific objectives are to determine the minimum land area required to produce a certain amount of cell medium-feedstock for CM production-on agricultural land and to identify potential future land use scenarios assuming that the macro components of the cell medium are solely produced from common agricultural crops in southern Germany. A linear programming model was developed to analyze four different scenarios of CM production, considering factors such as crop rotation, nutrient sourcing, and solar energy use. The results indicate that CM production using plants as raw material for the cell medium cannot improve land use efficiency substantially compared to conventional pork production. Extraction methods, crop choice, and energy sources will strongly influence future pathways for CM. We also find that there is no substantial benefit from CM in terms of climate change mitigation when feedstock is sourced solely from plants. This study provides valuable insights into the limitations of using agricultural feedstock for sustainable CM production. The findings suggest that future research should focus on optimizing the land use efficiency of CM. This includes exploring alternatives such as sourcing cell media from precision fermentation instead of relying solely on crops, and utilizing upcycling possibilities.